Heteropolyacid-assisted ball-milling modified micron zero-valent iron particles as well as preparation method and application thereof

By modifying micron-sized zero-valent iron particles through ball milling assisted by heteropolyacids, the reactivity and cost issues of micron-sized zero-valent iron in the degradation of trichloroethylene were solved, achieving efficient and stable trichloroethylene degradation.

CN119281404AActive Publication Date: 2025-01-10ZHEJIANG UNIV

Patent Information

Application Number
CN202411446605.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-10
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The reactivity of existing micron-sized zero-valent iron in degrading trichloroethylene is limited by the surface oxidation passivation process, resulting in poor electron transfer ability. Furthermore, the high cost of noble metal modification leads to limited reduction ability and difficulty in degrading byproducts.

Method used

A heteropolyacid-assisted ball milling modification method was used to mix and ball mill tungstic silicic acid, micron-sized iron, and ruthenium to prepare micron-sized zero-valent iron particles with ultra-low ruthenium loading. The reducing hydrogen generated by the catalytic cracking of the tungstic silicic acid surface was then used for the reduction of trichloroethylene.

Benefits of technology

It achieves efficient degradation in both low- and high-concentration trichloroethylene solutions, with a degradation efficiency of up to 95%, no degradation after more than 30 cycles, low cost, and stable performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281404A_ABST
    Figure CN119281404A_ABST
Patent Text Reader

Abstract

The invention discloses heteropolyacid-assisted ball-milling modified micron zero-valent iron particles as well as a preparation method and an application of the heteropolyacid-assisted ball-milling modified micron zero-valent iron particles. The micron zero-valent iron particles are mainly prepared by mixing micron zero-valent iron, heteropoly acid and a cheap precious metal compound. According to the specific preparation method, micron zero-valent iron, heteropoly acid and a precious metal compound are placed in a ball milling tank and in a specific atmosphere to be subjected to ball milling modification, and the heteropoly acid modified ultra-low-amount ruthenium loaded micron zero-valent iron particles are obtained. The particle provided by the invention has extremely strong reaction performance on chlorinated hydrocarbon, does not generate performance degradation after being cycled for more than 30 times, can realize complete dechlorination on low-concentration and high-concentration chlorinated hydrocarbon, and has extremely high water treatment application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of water treatment materials, and in particular relates to heteropolyacid-assisted ball-milling modified micron zero-valent iron particles, a preparation method and an application thereof. Background Art

[0002] Trichloroethylene (TCE) is a commonly used organic solvent and is carcinogenic. It has the characteristics of low viscosity, poor water solubility and high density. It can easily penetrate the soil and migrate to groundwater, and persist in groundwater for a long time, thus causing continuous harm to the environment and human health. Iron-based reducing materials can detoxify trichloroethylene through electron reduction dechlorination. Among them, micron zero-valent iron is cheaper than nano zero-valent iron and is more widely used in groundwater remediation projects. However, in actual engineering applications, the reactivity of micron zero-valent iron is often restricted by the surface oxidation passivation process, with poor electron transfer ability, limited reduction ability, and the presence of by-products such as dichloroethylene and dichloroethane in the reaction process. The degradation of such by-products is more difficult and the toxic effect is more significant. Atomic hydrogen is a strongly reducing species (-2.1evvs RHE), which can effectively avoid the disadvantage of incomplete dechlorination during the reduction process. Precious metals can induce hydrolysis to produce reducing hydrogen and can also produce active hydrogen species by cracking hydrogen. Due to the high price of precious metals, the high cost of precious metal-modified micron iron has limited its application. The price of the precious metal ruthenium is less than 1 / 5 of other common precious metals such as platinum, palladium, and silver. Therefore, using a lower loading amount of ruthenium to improve the electron transfer efficiency of micron-iron and induce the formation of bimetallic zero-valent iron between micron-iron and ruthenium, the resulting reducing active hydrogen species can completely reduce and dechlorinate chlorinated hydrocarbons, which is more conducive to achieving the remediation goal.

[0003] The extremely strong reducing property of atomic hydrogen can completely dechlorinate and detoxify chlorinated hydrocarbons, but the existence life of atomic hydrogen is extremely short, and most of the atomic hydrogen will be consumed during the hydrogen evolution process. Therefore, obtaining a micron iron material that can effectively regulate the anchoring and transfer of atomic hydrogen is the key to completely reducing chlorinated hydrocarbons. Summary of the invention

[0004] In order to solve the problems and defects existing in the background technology, the technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method and application of heteropoly acid-assisted ball milling modified micron zero-valent iron particles for degrading chlorinated hydrocarbons. The heteropoly acid provided is tungstosilicic acid. Hydrogen can be quickly transferred on the surface of micron iron modified by tungstosilicic acid, and cracked under the catalytic action of ruthenium to produce active hydrogen and stored in tungstosilicic acid for the reduction of chlorinated hydrocarbons.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] 1. A kind of heteropoly acid assisted ball milling modified micron zero-valent iron particles:

[0007] The micron zero-valent iron particles are mainly prepared by mixing micron zero-valent iron, heteropoly acid and precious metal compounds. The present invention mixes tungstosilicic acid, micron iron and relatively cheap precious metal ruthenium and performs mechanical ball milling to obtain heteropoly acid-modified ultra-low ruthenium-loaded micron zero-valent iron.

[0008] 2. A method for preparing micronized zero-valent iron particles assisted by ball milling with heteropolyacid:

[0009] Methods Micron zero-valent iron, heteropoly acid and noble metal compound are placed in a ball mill and subjected to ball milling modification in a specific atmosphere to prepare heteropoly acid-modified ultra-low ruthenium-loaded micron zero-valent iron particles.

[0010] The mass ratio of the zero-valent iron, tungstosilicic acid and ruthenium trichloride is 100:1:0.25-0.75.

[0011] After being placed in the ball mill jar, nitrogen was passed through the jar for 30 minutes, and the ball mill was performed at a ball mill speed of 600 rpm for 48 hours.

[0012] The particle size of the micron zero-valent iron is 38 μm.

[0013] The heteropoly acid is tungstosilicic acid, the noble metal compound is ruthenium trichloride, and the ball mill is a zirconium oxide type ball mill.

[0014] 3. An application of the above-mentioned heteropolyacid-assisted ball-milled modified micron zero-valent iron particles in the degradation of chlorinated hydrocarbon pollutants.

[0015] The degradation of chlorinated hydrocarbon pollutants refers to the removal of chlorinated hydrocarbon pollutants in groundwater.

[0016] 4. A method for degrading chlorinated hydrocarbon pollutants by using heteropolyacid-assisted ball-milling to modify micron zero-valent iron particles:

[0017] The method comprises first adjusting the pH of a chlorinated hydrocarbon pollutant solution to be degraded, then adding the obtained ball-milled modified micron zero-valent iron particles to the chlorinated hydrocarbon pollutant solution to be degraded after anaerobic aeration treatment, and then performing a closed oscillation reaction to achieve degradation. The concentration of chlorinated hydrocarbons in the reaction system is determined by gas chromatography.

[0018] The concentration of the modified micron zero-valent iron particles added to the chlorinated hydrocarbon pollutant solution to be degraded is 4 g / L.

[0019] The chlorinated hydrocarbon is trichloroethylene, and the concentrations of trichloroethylene in the specific experiments are 0.1 mM and 1 mM respectively.

[0020] The pH is adjusted to 7±1 by using NaOH or HCl, that is, the pH of the reaction system is set to 7±1, and the temperature of the reaction system is set to 25°C, and the speed of the constant temperature oscillating box during oscillation is 160rpm.

[0021] The micron zero-valent iron particles are added to a solvent to prepare a micron zero-valent iron particle solution containing 1 g / L, the prepared chlorinated hydrocarbon pollutant solution is injected into the micron zero-valent iron particle solution and placed in a serum bottle, and then the serum bottle is placed on a rotating incubator in a constant temperature box for reaction, and the concentration of trichloroethylene in the serum bottle is measured at intervals during the reaction process to obtain the effect of the scheme. The method for measuring the concentration of trichloroethylene adopts headspace gas chromatography to measure the concentration of trichloroethylene in the air part of the reaction bottle.

[0022] Compared with the prior art, the advantages of the present invention are:

[0023] 1. The present invention provides a preparation method and application of heteropoly acid-assisted ball-milled modified micron zero-valent iron particles. The particle size of the heteropoly acid-assisted ball-milled modified micron zero-valent iron particles is about 2 microns, and the iron content is higher than 90%wt.

[0024] 2. According to the scheme provided by the present invention, within 300 minutes, the degradation efficiency of 0.1 mM and 1 mM TCE by heteropolyacid-assisted ball-milling modified micron zero-valent iron is as high as 95%.

[0025] 3. Under the scheme provided by the present invention, within 15 days, the heteropoly acid-assisted ball-milled modified micron zero-valent iron can complete 30 cycles of degradation of 1 mM TCE, and the degradation ability does not decay.

[0026] In summary, the ruthenium-loaded micron zero-valent iron particles modified by heteropolyacid-assisted ball milling provided by the present invention have extremely strong reaction performance to chlorinated hydrocarbons, and the performance does not decay after more than 30 cycles. They can achieve complete dechlorination of both low-concentration and high-concentration chlorinated hydrocarbons, and have great application value in water treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 SEM image of the preparation of silane-stabilized nickel-doped nano-zero-valent iron;

[0028] Figure 2 This is a graph showing the effect of micron iron degrading 0.1 mM TCE;

[0029] Figure 2 This is the effect diagram of the prepared heteropoly acid ball-milling modified micron iron degrading 0.1mM TCE;

[0030] Figure 3 This is a diagram showing the effect of prepared heteropoly acid-assisted ball-milled ruthenium-based micronized iron on the degradation of 0.1 mM TCE;

[0031] Figure 4 This is a diagram showing the effect of prepared heteropoly acid-assisted ball-milled ruthenium-based micronized iron on the degradation of 1mM TCE;

[0032] Figure 5 This is a diagram showing the effect of prepared heteropoly acid-assisted ball-milled micronized iron in degrading 1mM TCE;

[0033] Figure 6 This is a comparison chart of the effect of prepared heteropoly acid-assisted ball-milled ruthenium-based micron iron in degrading 1mM TCE;

[0034] Figure 7 This is a diagram showing the effect of prepared heteropoly acid-assisted ball-milled ruthenium-based micronized iron on the degradation of 1mM TCE;

[0035] Figure 8 This is the effect diagram of the prepared ball-milled ruthenium-based micron iron degrading 1mM TCE;

[0036] Fig. 9 This is a diagram showing the effect of cyclic degradation of 1mM TCE by prepared heteropolyacid-assisted ball-milled ruthenium-based micron iron. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and specific operation process are given, but the protection authority of the present invention is not limited to the following embodiments.

[0038] In the following comparative tests and examples, unless otherwise specified, the raw materials and instruments used are commercially available, the processes used are conventional processes, the equipment used are conventional equipment, and the data obtained are the average values ​​of more than three repeated experiments.

[0039] Embodiments of the present invention are as follows:

[0040] Example 1

[0041] (1) Zirconia beads of different particle sizes (particle sizes of 2 mm, 4 mm, and 6 mm, with a total of 15 beads) were placed in a zirconia ball mill as sand mill media;

[0042] (2) 4 mg of tungstosilicic acid, 1 mg of ruthenium trichloride, and 0.4 g of 38-micron iron powder (mass ratio of 1:0.25:100) were placed in a ball mill and nitrogen was passed through the mill for 30 min;

[0043] (3) Turn on the ball mill, adjust the ball mill speed to 600 rpm, and ball mill for 48 hours to obtain heteropoly acid-assisted ball milling modified micron zero-valent iron particles.

[0044] The results show that Figure 1The particle size of the heteropolyacid-assisted ball-milled modified micron zero-valent iron particles is about 2 microns, the iron content is higher than 90%wt, and the ruthenium loading is less than 1%wt.

[0045] Accurately weigh 0.4 g of the heteropolyacid-assisted ball-milled ruthenium-based micronized zero-valent iron FSWRu prepared in this example. 0.25 (where the subscript 0.25 indicates the mass ratio of the added ruthenium trichloride to one part of tungstosilicic acid, the same below) was added to 100 mL of 1 mM TCE solution after nitrogen aeration with pH adjusted to 7, and sealed strictly. Oscillating in a constant temperature shaker, after 4 hours, 0.25 mL of top air was extracted from the sealed bottle with a gas sampling needle, and the concentration of TCE was detected by GC-FID. The micron zero-valent iron after the reaction was collected by centrifugation and the above degradation process of 1 mM TCE was repeated, and the number of cycles was 30.

[0046] The results show that if Fig. 9 As shown, FSWRu can complete 30 cycles of 1mM TCE within 15 days without any attenuation in cycle efficiency. Ruthenium-based micron-iron modified by tungstosilicic acid-assisted ball milling can enhance the reduction performance of micron-iron at ultra-low ruthenium loading, and has extremely strong cycle capacity, which has very high application value in water treatment.

[0047] Comparison test 1

[0048] Accurately weigh 0.4 g of the heteropolyacid-assisted ball-milled modified ruthenium-based micron zero-valent iron (FSWRu) prepared in Example 1. 0.25 ), micron zero-valent iron (mFe) and iron tungstosilicate (FSW) were added into 100 mL of 0.1 mM TCE solution after nitrogen aeration and sealed strictly.

[0049] The mixture was then shaken in a constant temperature shaker. At regular intervals, 0.25 ml of top air was extracted from the sealed bottle using a gas sampling needle, and the TCE concentration was detected using GC-FID.

[0050] The results show that if Figure 2 , Figure 3 and Figure 4 As shown, under anaerobic conditions, pure micron iron can only degrade TCE by 20% to 30% within 10 days, FSW can degrade TCE by more than 95% within 10 days, and the FSWRu of the present invention can completely degrade TCE within only one hour, with only alkane products and no other chlorinated by-products.

[0051] Comparison test 2

[0052] Same as Example 1, except that the chlorinated hydrocarbon is 1 mM TCE.

[0053] The results show that if Figure 5As shown, FSWRu prepared in Example 1 0.25 1 mM TCE can be completely degraded within 4 hours, with a degradation rate constant of 0.007 min -1 , Figure 6 As shown in Figure 2, ferrous tungstosilicate FSW can degrade TCE by 70% within 10 days, and the degradation rate constant is 0.097d -1 The unmodified micron iron has no obvious degradation ability for high concentration of TCE, indicating that the heteropolyacid-assisted ball-milled modified micron zero-valent iron has strong reducing performance and still has a high degradation efficiency for high concentration of TCE.

[0054] Example 2

[0055] With embodiment 1, difference is that the micron iron prepared by ball milling is respectively that raw material is 2mg ruthenium chloride, 0.4g 38 micron iron powder, and raw material is 4mg tungstosilicic acid, 2mg ruthenium chloride, 0.4g 38 micron iron powder.The ruthenium-based micron iron of utilizing ball milling to prepare and the ruthenium-based micron iron of heteropolyacid ball milling are added respectively to be 7 through the 100mL concentration after nitrogen aeration treatment through regulating pH to be 1mMTCE solution, strictly sealed.Then vibrate in constant temperature shaking table, at regular intervals, extract 0.25 milliliter of top air with gas phase sampling needle from sealed bottle, detect the concentration of TCE with GC-FID.

[0056] The results show that Figure 7 and Figure 8 As shown, the ball-milled ruthenium-based micronized iron FRu 0.5 The degradation rate constant of TCE is 0.003min -1 , Ruthenium-based micronized iron FSWRu assisted by ball milling 0.5 The degradation rate constant is 0.034min -1 , which is more than 10 times that of the noble metal and micron iron milled separately, indicating that the degradation ability of the noble metal micron iron assisted by the heteropoly acid milling is high.

[0057] The above description is only a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. Any person familiar with the technology can understand and think of any changes or substitutions within the technical scope disclosed by the present invention, which should be included in the scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A heteropolyacid-assisted ball-milling modified micron zero-valent iron particle, characterized in that: The micron zero-valent iron particles are mainly prepared by mixing micron zero-valent iron, heteropoly acid and noble metal compounds.

2. A method for preparing heteropolyacid-assisted ball-milling-modified micron zero-valent iron particles, characterized in that: Methods Micron zero-valent iron, heteropoly acid and noble metal compound were placed in a ball mill and subjected to ball milling modification in a specific atmosphere to obtain micron zero-valent iron particles.

3. The heteropolyacid-assisted ball-milling modified micron zero-valent iron particles according to claim 1 or the preparation method according to claim 2, characterized in that: The mass ratio of the zero-valent iron, tungstosilicic acid and ruthenium trichloride is 100:1:0.25-0.

75.

4. The heteropolyacid-assisted ball-milling modified micron zero-valent iron particles according to claim 1 or the preparation method according to claim 2, characterized in that: After being placed in the ball mill jar, nitrogen was passed through the jar for 30 minutes, and the ball mill was performed at a ball mill speed of 600 rpm for 48 hours.

5. The heteropolyacid-assisted ball-milling modified micron zero-valent iron particles according to claim 1 or the preparation method according to claim 2, characterized in that: The particle size of the micron zero-valent iron is 38 μm.

6. The heteropolyacid-assisted ball-milling modified micron zero-valent iron particles according to claim 1 or the preparation method according to claim 2, characterized in that: The heteropoly acid is tungstosilicic acid, the noble metal compound is ruthenium trichloride, and the ball mill is a zirconium oxide type ball mill.

7. Use of the heteropolyacid-assisted ball-milled modified micron zero-valent iron particles according to claim 1 or the heteropolyacid-assisted ball-milled modified micron zero-valent iron particles prepared by the preparation method according to any one of claims 2 to 6 in the degradation of chlorinated hydrocarbon pollutants.

8. A method for degrading chlorinated hydrocarbon pollutants using the heteropolyacid-assisted ball-milled modified micron zero-valent iron particles of claim 1 or the heteropolyacid-assisted ball-milled modified micron zero-valent iron particles prepared by the preparation method of any one of claims 2 to 6, characterized in that: The method comprises the following steps: firstly adjusting the pH of a chlorinated hydrocarbon pollutant solution to be degraded, then adding the obtained ball-milled modified micron zero-valent iron particles into the chlorinated hydrocarbon pollutant solution to be degraded after anaerobic aeration treatment, and then performing a closed oscillation reaction to achieve degradation.

9. The method for degrading chlorinated hydrocarbon pollutants by using heteropolyacid-assisted ball-milling to modify micron zero-valent iron particles according to claim 8, characterized in that: The concentration of the modified micron zero-valent iron particles added to the chlorinated hydrocarbon pollutant solution to be degraded is 4 g / L.

10. The method of claim 9 for degrading chlorinated hydrocarbon pollutants by using heteropolyacid-assisted ball-milling to modify micronized zero-valent iron particles, characterized in that: The pH is adjusted to 7±1 by using NaOH or HCl, that is, the pH of the reaction system is set to 7±1, and the temperature of the reaction system is set to 25°C, and the speed of the constant temperature oscillating box during oscillation is 160rpm.

Citation Information

Patent Citations

  • Method for efficiently removing heavy metal ions on basis of ball-milled oxalated zero-valence iron

    CN108911101A

  • Transition metal phosphide modified nano-iron composite material, preparation method and application thereof

    CN113649034A

  • Sodium silicate modified zero-valent iron composite material as well as preparation method and application thereof

    CN114735799A

  • Tungsten silicic acid micron zero-valent iron material as well as preparation method and application thereof

    CN115255347A

  • Preparation method for preparing iron-nitrogen compound modified zero-valent iron material through mechanochemical method and application of iron-nitrogen compound modified zero-valent iron material

    CN117509872A

Cited By

  • Solid acid doped iron-carbon composite material mediated long-acting permeable reactive barrier technology

    CN120515384A